Monitoring the effects of biocide treatment of Pseudomonas fluorescens biofilms formed under different flow regimes - Simões, M. (2003)
The effectiveness of glutaraldehyde (GTA), a very common biocide for controlling biofilms formed by Pseudomonas fluorescens on stainless steel slides, in laminar and turbulent flow, was investigated. Tests were performed using a concentration of biocide of 200 mg Lˉ¹ and a range of exposure times. The GTA action was assessed by means of activity tests and dry weight of the biofilms. The physical stability of the biofilm without biocide application and after exposure to GTA for different periods of time was also studied and evaluated through the variation of the mass of the deposit after submission to different rotation velocities. The results showed that, in all the situations studied, biofilms were not controlled after the treatment with biocide, since they remained on the metal surface and were still active. The results also demonstrated that the physical stability of the biofilms increased with biocide application.